2011
DOI: 10.1371/journal.pone.0020875
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Trial of the Knowledge Impact of Tuberculosis Information Leaflets among Staff Supporting Substance Misusers: Pilot Study

Abstract: BackgroundInformation leaflets are widely used to increase awareness and knowledge of disease. Limited research has, to date, been undertaken to evaluate the efficacy of these information resources. This pilot study sought to determine whether information leaflets developed specifically for staff working with substance mis-users improved knowledge of tuberculosis (TB).MethodStaffs working with individuals affected by substance mis-use were recruited between January and May 2008. All participants were subjectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
(24 reference statements)
0
5
0
1
Order By: Relevance
“…The study also identified room for improvement in TB health literacy, particularly, for improved education about key TB concepts, such as the difference between LTBI and active TB and for education about the meaning of screening test results. There is evidence that the use of information leaflets can improve knowledge about TB ( Roy et al, 2011 ). By improving the care provided to HCWs with LTBI it may be possible not only to reduce active TB infections in this group, but also for the vulnerable people they care for.…”
Section: Discussionmentioning
confidence: 99%
“…The study also identified room for improvement in TB health literacy, particularly, for improved education about key TB concepts, such as the difference between LTBI and active TB and for education about the meaning of screening test results. There is evidence that the use of information leaflets can improve knowledge about TB ( Roy et al, 2011 ). By improving the care provided to HCWs with LTBI it may be possible not only to reduce active TB infections in this group, but also for the vulnerable people they care for.…”
Section: Discussionmentioning
confidence: 99%
“…The survey was designed selecting relevant questions from previous published studies [4, 6, 911], and based on current Mozambican National Tuberculosis Program (NTP) guidelines, after consensus from a team including clinicians, a social scientist and an epidemiologist with experience in TB and KAP studies. The survey was conducted in an interview format as a standard, but self-administered if the HCW repeatedly (more than two times) reported they had insufficient time for an interview.…”
Section: Methodsmentioning
confidence: 99%
“…Good understanding of TB disease management is often inadequate even in the context of recent TB training [4]. By contrast, other studies suggest that TB knowledge pre-training is satisfactory and may even improve following brief education [911]. While the results of a once-off training program can be inconsistent, there are examples of how periodic training and supervision can improve HCWs’ TB knowledge and skills [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Targeted provision of information to raise awareness among high-risk groups, in the form of leaflets or through the Internet, has been used for diseases other than TB, such as diabetes, HIV or breast cancer [55,56].…”
Section: General Backgroundmentioning
confidence: 99%